2018
DOI: 10.26717/bjstr.2018.10.001998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cortisol on Bovine Oocytes Maturation and Further Embryonic Development After In vitro Fertilization

Abstract: Oocyte meiotic maturation and further embryonic development after fertilization is one of the most important physiological requirements for species survival. Herein, the aim of the study was to evaluate the effects of the stressful hormone, cortisol, on the nuclear maturation and further embryonic development of bovine oocytes after in vitro fertilization (IVF). For such purpose, 1,439 immature oocytes were collected from slaughtered cows and matured in vitro for 24 hours with different concentrations of corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 41 publications
(52 reference statements)
4
13
1
Order By: Relevance
“…This finding is consistent with other studies that demonstrated a similar role of ERK1/2 activation, along with AKT and their downstream phosphorylation activity during IVM of mouse and bovine oocytes [13,14,30,75,78]. identified that exposure of immature oocytes to several concentrations of cortisol in the maturation medium resulted in a concentration-dependent decrease in maturation and subsequent cleavage rate [12]. They assessed maturation progression after a 22-24 h period in which oocytes (n = 412) were incubated in cortisol at concentrations of 0 (control), 50, 150 and 250 µM [12].…”
Section: The Effects Of Glucocorticoid Exposure On Oocyte Maturation and Early Embryonic Developmentsupporting
confidence: 93%
See 4 more Smart Citations
“…This finding is consistent with other studies that demonstrated a similar role of ERK1/2 activation, along with AKT and their downstream phosphorylation activity during IVM of mouse and bovine oocytes [13,14,30,75,78]. identified that exposure of immature oocytes to several concentrations of cortisol in the maturation medium resulted in a concentration-dependent decrease in maturation and subsequent cleavage rate [12]. They assessed maturation progression after a 22-24 h period in which oocytes (n = 412) were incubated in cortisol at concentrations of 0 (control), 50, 150 and 250 µM [12].…”
Section: The Effects Of Glucocorticoid Exposure On Oocyte Maturation and Early Embryonic Developmentsupporting
confidence: 93%
“…Oocytes and follicular diameters were also found to be significantly reduced at all exposure concentrations of cortisol compared to controls. Contrary to da Silva et al (2018) and González et al (2010), the activation rates of oocytes increased when follicles were exposed to 1, 5 and 10 ng/mL cortisol post-culture [17]. However, findings related to oocyte quality and development potential were in support of findings from both earlier studies [12,15].…”
Section: The Effects Of Glucocorticoid Exposure On Oocyte Maturation and Early Embryonic Developmentsupporting
confidence: 77%
See 3 more Smart Citations